Three Years of Salvage IMRT for Prostate Cancer: Results of the Montpellier Cancer Center. (20th March 2012) - Riou, Olivier; Fenoglietto, Pascal; Laliberté, Benoit; Menkarios, Cathy; Llacer Moscardo, Carmen; Hay, Meng Huor; Ailleres, Norbert; Dubois, Jean-Bernard; Rebillard, Xavier; Azria, David
Abstract : Background . To assess the feasibility of salvage intensity-modulated radiation Therapy (IMRT) and to examine clinical outcome. Patients and Methods . 57 patients were treated with salvage IMRT to the prostate bed in our center from January, 2007, to February, 2010. The mean prescription dose was 68 Gy in 34 fractions. Forty-four patients received concomitant androgen deprivation. Results . Doses to organs at risk were low without altering target volume coverage. Salvage IMRT was feasible without any grade 3 or 4 acute gastrointestinal or urinary toxicity. With a median follow-up of 21 months, one grade 2 urinary and 1 grade ≥ 2 rectal late toxicities were reported. Biological relapse-free survival was 96.5% (2.3% (1/44) relapsed with androgen suppression and 7.7% (1/13) without). Conclusion . Salvage IMRT is feasible and results in low acute and chronic side-effects. Longer follow-up is warranted to draw conclusions in terms of oncologic control.